2020
DOI: 10.1016/j.ebiom.2020.102904
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myelomonocytic leukaemia stem cell transcriptomes anticipate disease morphology and outcome

Abstract: Background Chronic myelomonocytic leukaemia (CMML) is a clinically heterogeneous stem cell malignancy with overlapping features of myelodysplasia and myeloproliferation. Over 90% of patients carry mutations in epigenetic and/or splicing genes, typically detectable in the Lin − CD34 + CD38 − immunophenotypic stem cell compartment in which the leukaemia-initiating cells reside. Transcriptional dysregulation at the stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…This effect was more obvious after 96 h of TNF-α treatment than 24 h. The findings also indicated that some transcription factors, including CEBPB, NFKB1, JUN, RELA, and EGR1, mediated the TNF-α-induced differentiation of ADSCs into mononuclear leukocytes. These included regulons centered on NFKB1, IRF8, RELA, RELB, IRF7, and other transcription factors that are strongly associated with monocytic lineage differentiation and whose interaction may be relevant to myeloid cell survival and development [ 29 , 30 ]. Thus, these results suggest that TNF-α treatment would enhance the potential of ADSCs to differentiate into immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was more obvious after 96 h of TNF-α treatment than 24 h. The findings also indicated that some transcription factors, including CEBPB, NFKB1, JUN, RELA, and EGR1, mediated the TNF-α-induced differentiation of ADSCs into mononuclear leukocytes. These included regulons centered on NFKB1, IRF8, RELA, RELB, IRF7, and other transcription factors that are strongly associated with monocytic lineage differentiation and whose interaction may be relevant to myeloid cell survival and development [ 29 , 30 ]. Thus, these results suggest that TNF-α treatment would enhance the potential of ADSCs to differentiate into immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…This technique also revealed considerable interpatient heterogeneity in myelofibrosis with respect to their different patterns of clonal evolution [55]. Regarding chronic myelomonocytic leukemia (CMML), transcriptome profiling of single cells identified CMML stem cells that transcriptionally resembled normal HSCs and differentiated between CMML-1 and CMML-2 stem cells, which can be distinguished clinically only by the percentages of their blasts and promonocytes [113]. Likewise, samples from patients with MDS del(5q) were assessed by scDNA-seq before and after lenalidomide treatment to infer their clonal architecture and found to have a high degree of intratumoral heterogeneity [114].…”
Section: Single-cell Studies In Hematological Malignanciesmentioning
confidence: 99%
“…The fraction of bone marrow blast cells distinguishes CMML-0, CMML-1 and CMML-2, the latter category being defined by a fraction of blast cells between 10% and 20% of bone marrow cells and the worst outcome. Comparing single cell gene expression in CMML-0/1 and CMML-2, Wiseman et al [4] identify striking segregation of CMML-2 CD34 + CD38 À cells, which is nicely illustrated by pseudotime ordering analysis. Interestingly, such a transcriptome-based dichotomy was not observed between dysplastic and proliferative CMML, the other distinctive categories identified by the WHO.…”
mentioning
confidence: 97%
“…In this issue of EBioMedicine, Wiseman et al [4] analyze gene expression at the single cell level to track CMML diversity within and between individual patients. They focus on sorted bone marrow Lin À CD34 + CD38 À cells, a cell population enriched in disease initiating cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation